Ultra-low temperature water-gas shift reaction catalyzed by homogeneous Ru-complexes in a membrane reactor - membrane development and proof of concept - Logemann, Morten; Wolf, Patrick; Loipersböck, Jürgen; Schrade, Alexander; Wessling, Matthias; Haumann, Marco (Catalysis: Science and Technology, 2021)
A monolithic membrane reactor combining the supported ionic liquid-phase (SILP) catalyzed ultra-low temperature water-gas shift reaction (WGSR) within situproduct removal is presented. The SILP catalyst consists of the transition metal complex [Ru(CO)3Cl2]2homogeneously dissolved in 1-butyl-2,3-dimethylimidazolium chloride [C4C1C1Im]Cl and supported on alumina pellets. These Ru-SILP pellets are deposited inside the channels of a silicon carbide monolith. The resulting monolithic catalyst is very active and stable in the WGSR in the temperature range between 120 and 160 °C, thereby making full use of the high equilibrium conversion at these conditions. A facilitated transport membrane was coated onto the smooth outside of the SiC monolith to allow preferential removal of CO2compared to H2. The proof of this concept has been shown under industrially relevant conditions using a biogas feed. These results demonstrate, for the first time, the combination of homogeneous SILP catalyzed WGSR with enhancedin situremoval of one of the products (here: CO2)viafacilitated transport membrane separation.
CRIS-Team Scopus Importer:2021-03-19